2005
DOI: 10.1098/rspb.2004.2853
|View full text |Cite
|
Sign up to set email alerts
|

The invasive Korea and Japan types ofVarroa destructor, ectoparasitic mites of the Western honeybee (Apis mellifera), are two partly isolated clones

Abstract: Varroa destructor , now a major pest of the Western honeybee, Apis mellifera , switched from its original host, the Eastern honeybee, A. cerana , ca . 50 years ago. So far, only two out of several known mitochondrial haplotypes of V. destructor have been found to be capable of reproducing on A. mellifera (Korea and Japan). These haplotypes are associated in almost complete cytonuc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
156
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 143 publications
(169 citation statements)
references
References 34 publications
11
156
1
Order By: Relevance
“…The European honeybee does not express these traits at a level at which they confer tolerance to the parasite ). This became obvious after the mite shifted host from A. cerana to A. mellifera L. (Rath and Drescher 1990;Solignac et al 2005) and became responsible for the mortality of a large number of honeybee colonies in several regions of the world where it has spread (see references in Dietemann et al 2012;van Dooremalen et al 2013;Spleen et al 2013;Steinhauer et al 2014). Apis mellifera colonies cannot survive without chemical treatment against Varroa mites and colonies usually die within one to three years if left untreated (Martin 1998;Rosenkranz et al 2010).…”
Section: Introductionmentioning
confidence: 99%
“…The European honeybee does not express these traits at a level at which they confer tolerance to the parasite ). This became obvious after the mite shifted host from A. cerana to A. mellifera L. (Rath and Drescher 1990;Solignac et al 2005) and became responsible for the mortality of a large number of honeybee colonies in several regions of the world where it has spread (see references in Dietemann et al 2012;van Dooremalen et al 2013;Spleen et al 2013;Steinhauer et al 2014). Apis mellifera colonies cannot survive without chemical treatment against Varroa mites and colonies usually die within one to three years if left untreated (Martin 1998;Rosenkranz et al 2010).…”
Section: Introductionmentioning
confidence: 99%
“…It remains to be clarified whether the survival of the Arnot Forest bees and the Italian bees on Fernando de Noronha is due to an adaptive resistance by the host, host tolerance to mite infestation, or reduced virulence by the mite either by the mite's haplotype or adaptive reduced virulence. While many of these populations reviewed here clearly demonstrate adapted host resistance or at least tolerance, investigations have been very bee-centric, likely due to the common acceptance that the Varroa mite has a low genetic variation in Europe due to its clonal origin (Solignac et al 2005). A deeper understanding of the mite's passive or active role in the co-evolution among all of these populations would be insightful.…”
Section: Mite-resistant Mechanismsmentioning
confidence: 99%
“…A paradox often encountered in genetic studies of invasive species, is a colonization success of the introduced populations despite a strong reduction of genetic diversity (Frankham 2005; see also reviews by Dlugosch andParker 2008 andRoman andDarling 2007). Several studies to date have shown that founder effects and bottlenecks are not an obstacle for invasion success (Ahern et al 2009;Puillandre et al 2008;Solignac et al 2005), whereas plasticity in life history traits seems to be important for the successful expansion of an invasive species (Chen et al 2006;Valiente et al 2010;Wang et al 2005). Mites belonging to clade I have been found across a wide range of habitats and regions beyond the predicted geographical distribution as modeled based on climatic suitability T. evansi ).…”
Section: Species-wide Genetic Homogeneity and Invasion Eventsmentioning
confidence: 99%